Differential effects of abstract and concrete processing on the reactivity of basic and self-conscious emotions. Issue 4 (19th May 2021) - Bornstein, Oren; Katzir, Maayan; Simchon, Almog; Eyal, Tal
ABSTRACT: The present research examines the influence of different processing modes (abstract vs. concrete) on the intensity of negative basic emotions (anger, fear) and self-conscious emotions (guilt, shame). We suggest that the cognitive appraisals underlying self-conscious emotions are relatively more abstract and less concrete than the appraisals underlying basic emotions. Consequently, we predicted that abstract processing would increase the intensity of self-conscious emotions and decrease the intensity of basic emotions, whereas concrete processing would increase the intensity of basic emotions and decrease the intensity of self-conscious emotions. We tested this prediction in four experiments. In Experiments 1 and 2, concrete processing led to more intense anger than abstract processing, and abstract processing led to more intense guilt than concrete processing. In Experiment 3a, concrete processing increased the intensity of fear, and in Experiment 3b, concrete processing decreased the intensity of shame. Our findings highlight the importance of considering the emotion's underlying appraisals when reflecting on one's emotional experience.